The New Index Numbers of the United States Bureau of Labor Statistics - Wright, P. G.; Mitchell, Wesley C. (Quarterly Journal of Economics, 1916)
P. G. Wright; The New Index Numbers of the United States Bureau of Labor Statistics, The Quarterly Journal of Economics, Volume 30, Issue 4, 1 August 1916,